Prevalence of posttraumatic stress disorder in orthopedic trauma patients and a call to implement the Injured Trauma Survivor Screen as a prospective screening protocol in the United States - Victoria J. Nedder; Mary A. Breslin; Vanessa P. Ho; Heather A. Vallier (Journal of Trauma and Injury)
Purpose Posttraumatic stress disorder (PTSD) is prevalent and is associated with protracted recovery and worse outcomes after injury. This study compared PTSD prevalence using the PTSD checklist for DSM-5 (PCL-5) with the prevalence of PTSD risk using the Injured Trauma Survivor Screen (ITSS). Methods Adult trauma patients at a level I trauma center were screened with the PCL-5 (sample 1) at follow-up visits or using the ITSS as inpatients (sample 2). Results Sample 1 (n=285) had significantly fewer patients with gunshot wounds than sample 2 (n=45) (8.1% vs. 22.2%, P=0.003), nonsignificantly fewer patients with a fall from a height (17.2% vs. 28.9%, P=0.06), and similar numbers of patients with motor vehicle collision (40.7% vs. 37.8%, P=0.07). Screening was performed at a mean of 154 days following injury for sample 1 versus 7.1 days in sample 2. The mean age of the patients in sample 1 was 45.4 years, and the mean age of those in sample 2 was 46.1 years. The two samples had similar proportions of female patients (38.2% vs. 40.0%, P=0.80). The positive screening rate was 18.9% in sample 1 and 40.0% in sample 2 (P=0.001). For specific mechanisms, the positive rates were as follows: motor vehicle collisions, 17.2% in sample 1 and 17.6% in sample 2 (P>0.999); fall from height, 12.2% in sample 1 and 30.8% in sample 2 (P=0.20); and gunshot wounds, 39.1% in sample 1 and 80.0% in sample 2 (P=0.06). Conclusions The ITSS was obtained earlier than PCL-5 and may identify PTSD in more orthopedic trauma patients. Differences in the frequency of PTSD may also be related to the screening tool itself, or underlying patient risk factors, such as mechanism of injury, or mental or social health.